2022
DOI: 10.1021/acsnanoscienceau.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Self-Induced Core–Shell InAlN Nanorods: Formation and Stability Unraveled by Ab Initio Simulations

Abstract: By addressing precursor prevalence and energetics using the DFT-based synthetic growth concept (SGC), the formation mechanism of self-induced InAlN core−shell nanorods (NRs) synthesized by reactive magnetron sputter epitaxy (MSE) is explored. The characteristics of In-and Al-containing precursor species are evaluated considering the thermal conditions at a typical NR growth temperature of around 700 °C. The cohesive and dissociation energies of In-containing precursors are consistently lower than those of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…24,25 Low-dimensional systems of similar complexity and their electronic and topological properties including in relation to electronic applications have already been studied by using commercial DFT software. 26,27 Accordingly, such mechanisms are certain to be significant for controlling electron transport properties in the systems with BP.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Low-dimensional systems of similar complexity and their electronic and topological properties including in relation to electronic applications have already been studied by using commercial DFT software. 26,27 Accordingly, such mechanisms are certain to be significant for controlling electron transport properties in the systems with BP.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, published work on the growth mechanism of semiconductor NWs on graphene films is sparse. Detailed theoretical studies that have been reported include the following: Wallentin et al theoretically explained the in-plane and vertical growth mechanism of Au-catalyzed III–V NWs on a graphite substrate by using Young’s equation at the graphite-liquid–vapor boundary; Kumaresan et al proposed a model to illustrate the interfacial strain at NW nucleation partitions between graphene and GaN nucleus and successfully explained the relationship between NW height and number of graphene layers underneath; Sangiovanni et al employed density-functional molecular dynamics to identify the atomic pathway and nucleation mechanisms on graphene surface; and Alves Machado Filho et al have successfully addressed the formation and stability of self-induced core–shell InAlN nanorods by higher-level ab initio simulations. However, self-organized epitaxial growth of NW on a graphene film without any catalyst or intermediate layer during its initial nucleation stage is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…39 Meanwhile, Xie et al showed that both symmetric and asymmetric twins can exist in polar boron carbide, and they provided the precise atomic structure of the TBs by using ab initio simulations. 40 Therefore, both ab initio MD simulation 41,42 and classical MD simulation 19 can be applied to the analysis and calculation of complex material systems such as boron carbide. Recently, the DFT simulation results revealed that imposing nanoscale twins can increase the theoretical shear strength of boron carbide ceramics by 11% and the compressive shear strength by 12%, thereby proving the strengthening effect of nanotwins.…”
Section: Introductionmentioning
confidence: 99%